Alat Sebagai Alat Bukti Dalam Tindak Pidana Narkotika - Mahaneni Rosaning Kinasih (Faculty of Law, Universitas Airlangga, 2021)
AbstractIn the case of Narcotics Crime, verification is one of the important process, because in this process we can know how the criminal act can be done and to make that the defendant is the guilty one. Indeed based on judge confidence and all the evidence. In Law Number 35 of 2009 Concerning Narcotics, Article 101 Paragraph (1) regulates that: